2023
DOI: 10.1186/s12888-023-05244-3
|View full text |Cite
|
Sign up to set email alerts
|

Positive mental health in adults with bipolar disorder: exploring social support subtypes, negative social interactions and potential to flourish

Ken Fowler,
Kaya E. Dooley

Abstract: Background Bipolar disorder (BD) (i.e., BD-I or BD-II) is a serious mental illness (SMI) that can cause significant life challenges, but its impact and management may be mediated by psychosocial factors. This study’s primary objectives were to investigate whether adults with BD differ from those without in terms of social support, negative social interactions (NSIs), and positive mental health (PMH). Secondly, examine whether gender differences exist in terms of these variables, as well as whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Clarifying the relationship between perceived social connectedness and STBs may be particularly important in the context of COVID-19. Research consistently indicates that patients with BD exhibit lower perceived social connection than healthy controls (Eidelman et al 2012 ; Fowler and Dooley 2023 ; Furukawa et al 1999 ; Xie et al 2018 ). Many studies have reported an increase in loneliness since the start of the COVID-19 pandemic in accordance with social distancing regulations (Buecker and Horstmann 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Clarifying the relationship between perceived social connectedness and STBs may be particularly important in the context of COVID-19. Research consistently indicates that patients with BD exhibit lower perceived social connection than healthy controls (Eidelman et al 2012 ; Fowler and Dooley 2023 ; Furukawa et al 1999 ; Xie et al 2018 ). Many studies have reported an increase in loneliness since the start of the COVID-19 pandemic in accordance with social distancing regulations (Buecker and Horstmann 2022 ).…”
Section: Introductionmentioning
confidence: 99%